Theoretical aspects related to the creation of algorithm for quality costs measurement system - Velkoska, Cvetanka; Tomov, Mite; Kuzinovski, Mikolaj (Journal of Production Engineering, 2018)
This paper presents the theoretical aspects taken into account when creating an algorithm for a quality costs measurement system, developed using a descriptive-analytical method. The methodological approach relies on the systemic thinking about management of success, including the elements of integration, innovation and agility, taken into account when developing the scope, rules, criteria, possibilities and alternatives. The proposed algorithm provides a structured approach and systematic measurement of the quality costs, which, in turn provides for better understanding, detection and correction of the errors on the spot where they actually occurred and not where they appeared. This ensures the timeliness, accuracy and reliability of the data and information about the costs of quality, opens possibilities not only for diagnostic analytics but also for predictive and prescriptive analytics, which increases the efficiency of the company.